Local to national: Thailand’s Integrated Nutrition Program - Gillespie, Stuart; Tontisirin, Krasisid; Zseleczky, Laura (International Food Policy Research Institute, 2016)
THAILAND REDUCED CHILD undernutrition by more than half within one decade—an achievement recognized by the nutrition community as one of the best examples of a successful national nutrition program. Underweight rates among children under five decreased from more than 50 percent to less than 20 percent from 1982 to 1991, and severe and moderate underweight rates were nearly eliminated. The underweight rate was further reduced to 10 percent by 1996 and to 9 percent by 2012. Maternal care interventions were also successful. Thailand improved the reach of antenatal care—coverage increased from 35 percent in 1981 to near 95 percent in 2006. And iron-deficiency anemia prevalence among pregnant women was reduced from nearly 60 percent in the 1960s to 10 percent in 2005.